Introduction to the Symposium: Effects of Light Pollution Across Diverse Natural Systems. (12th July 2021) - Kernbach, Meredith E; Miller, Colleen; Alaasam, Valentina; Ferguson, Stephen; Francis, Clinton D
Synopsis: Light pollution, or the presence of artificial light at night (ALAN), is among the fastest growing but least understood anthropogenic stressor on the planet. While historically light pollution has not received attention comparable to climate change or chemical pollution, research over the past several decades has revealed the plethora of negative effects on humans, animals, and supporting ecosystems. As light pollution continues to grow in spatial, spectral, and temporal extent, we recognize the urgent need to understand how this affects circadian physiology, organismal fitness, life history traits and tradeoffs, population trends, and community interactions. Here, we aim to highlight background and foundational evidence of the effects of light pollution to present context and the basis for early light pollution studies. Next, we touch on several understudied topics where research is underway to fill gaps in our knowledge and provide the basis for future research. Last, we focus on questions that are vital to understanding the effects of ALAN on diverse natural systems and discuss the barriers we face conducting research on light pollution.